2016
DOI: 10.1007/s11103-016-0482-7
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory function of Arabidopsis lipid transfer protein 1 (LTP1) in ethylene response and signaling

Abstract: Ethylene as a gaseous plant hormone is directly involved in various processes during plant growth and development. Much is known regarding the ethylene receptors and regulatory factors in the ethylene signal transduction pathway. In Arabidopsis thaliana, REVERSION-TO-ETHYLENE SENSITIVITY1 (RTE1) can interact with and positively regulates the ethylene receptor ETHYLENE RESPONSE1 (ETR1). In this study we report the identification and characterization of an RTE1-interacting protein, a putative Arabidopsis lipid t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 56 publications
0
21
0
1
Order By: Relevance
“…These ethylene-induced ERFs were chosen based on information from The Arabidopsis Information Resource (TAIR) (http://www. arabidopsis.org/) and Wang et al (2016). Our assays indicated that the transcript levels for almost all the examined ERFs in the CPR5-OX (#OX3 and #OX7) were higher than those in the wild type, indicating that increased CPR5 transcript levels promote expression of downstream ERFs in these plants ( Figure 3A).…”
Section: Cpr5 Overexpression Enhances the Ethylene Response And Signamentioning
confidence: 84%
See 3 more Smart Citations
“…These ethylene-induced ERFs were chosen based on information from The Arabidopsis Information Resource (TAIR) (http://www. arabidopsis.org/) and Wang et al (2016). Our assays indicated that the transcript levels for almost all the examined ERFs in the CPR5-OX (#OX3 and #OX7) were higher than those in the wild type, indicating that increased CPR5 transcript levels promote expression of downstream ERFs in these plants ( Figure 3A).…”
Section: Cpr5 Overexpression Enhances the Ethylene Response And Signamentioning
confidence: 84%
“…To examine the effect of CPR5‐OX on the endogenous transcript levels of ethylene responsive factors ( ERFs ) in the Arabidopsis CPR5 ‐ OX transgenic plants, nine genes ( ERF1 , 2 , 4 , 5 , 8 , 9 , 11 , 104 , and 105 ) were chosen for quantitative RT‐PCR analysis. These ethylene‐induced ERFs were chosen based on information from The Arabidopsis Information Resource (TAIR) (http://www.arabidopsis.org/) and Wang et al (). Our assays indicated that the transcript levels for almost all the examined ERFs in the CPR5 ‐ OX (# OX3 and # OX7 ) were higher than those in the wild type, indicating that increased CPR5 transcript levels promote expression of downstream ERFs in these plants (Figure A).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The plant mbSUS has been successfully used to screen for potential interactions among membrane and signalling proteins of Arabidopsis thaliana (Jones et al, 2014;Lalonde et al, 2010) or for putative targets of chloroplast import receptors (Dutta, Teresinski, & Smith, 2014). Additionally, this approach is often applied to validate interactions with membrane proteins (Anne et al, 2015;Karnik et al, 2015;Wang, Sun, et al, 2016;Zhang et al, 2015).…”
Section: Direct Interactions Revealed By Y2h Screensmentioning
confidence: 99%